ANALISIS MATURITY SISTEM INFORMASI MANAJEMEN RUMAH SAKIT DOMAIN SERVICE OPERATION FRAMEWORK ITIL V3 - Aryanto; Arribe, Edo (Jurnal Rekayasa Perangkat Lunak dan Sistem Informasi, 2023)
At present the world has entered the 4.0 era where information technology is a major factor in theadvancement of agency services and hospitals are one of them. XYZ Hospital is a health agency thatprovides health services to the community and has a duty to provide comfort and quality in its services.Hospital Management Information System (SIMRS) is a system or information technology that is usefulfor supporting services in hospitals. In connection with the use of information technology in services atXYZ Hospital, management is needed so that the process of using information technology can bemeasured. The measurement was carried out to find out how much the SIMRS readiness was insupporting the existing services at the hospital. In this study, analysis of information technologymanagement uses the Information Technology Infrastructure Library (ITIL) version 3 framework in theService Operation domain. The results of this study are a maturity level value of 3.17 which is at level3, namely Defined which is obtained from the results of the questionnaire as an instrument andrecommendations from measurements that have been carried out and focus on reaching level 4, namelyManaged